2015
DOI: 10.1016/j.sbspro.2015.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Vocabulary Learning Strategies among EFL Iranian Medical Sciences Students

Abstract: Vocabulary learning strategies have dominated the subject of language learning for over two decades. This study aimed to investigate the use and preferences of these Strategies among the students at Rafsanjan University of Medical Sciences. One hundred eighty five students with different majors participated in this study. The instrument utilized was a modified version of Gu and Johnson questionnaire which consisted of 45 items related to the students' approach to vocabulary learning. The data were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 17 publications
4
22
2
Order By: Relevance
“…These are the strategies of (a) using contextual guessing (80.0%), (b) asking classmates about the meaning of new words (85.0%), and (c) using English-Arabic dictionaries (88.3%).This finding is in line with Schmitt's (1997), Al-Fuhaid's (2004) and Rabadi's (2016) studies, which reported that using bilingual dictionary strategy was the most frequently used by respondents. In addition, this finding is consistent with Schmitt's (1997), Fan's (2003), Al-Fuhaid's (2004), Kulikova's (2015) and Hashemi and Hadavi's (2015) studies, in which, guessing strategy was the most frequently used by their respondents. Both strategies of using instant on-screen computer translation programmes and using the Microsoft Word Thesaurus icon registered lower frequency use by respondents.…”
Section: Findings On Discovery Strategiessupporting
confidence: 88%
“…These are the strategies of (a) using contextual guessing (80.0%), (b) asking classmates about the meaning of new words (85.0%), and (c) using English-Arabic dictionaries (88.3%).This finding is in line with Schmitt's (1997), Al-Fuhaid's (2004) and Rabadi's (2016) studies, which reported that using bilingual dictionary strategy was the most frequently used by respondents. In addition, this finding is consistent with Schmitt's (1997), Fan's (2003), Al-Fuhaid's (2004), Kulikova's (2015) and Hashemi and Hadavi's (2015) studies, in which, guessing strategy was the most frequently used by their respondents. Both strategies of using instant on-screen computer translation programmes and using the Microsoft Word Thesaurus icon registered lower frequency use by respondents.…”
Section: Findings On Discovery Strategiessupporting
confidence: 88%
“…However, some students can acquire the language successfully while others fail. Thus, one student with others may have different Vocabulary Learning Strategies Several studies have been done to investigate vocabulary learning strategies used by English as a Foreign Language students, such as Afshar, Moazzam & Arbaby (2014) and Hashemi & Hadavi (2015). Afshar, Moazzam & Arbaby (2014) investigated vocabulary learning strategies used by 173 EFL (undergraduate) students in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the result showed the vocabulary strategy used by the learners frequently. Hashemi & Hadavi (2015) conducted an investigation on the use of vocabulary learning strategies among 185 EFL students in Iran. The reseachers adopted Gu and Johnson questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Le [12] focuses on almost a similar set of strategies with the addition of device-assisted strategies instead of social strategies. Furthermore, Hashemi & Hadavi [13] mention eight vocabulary learning strategies including dictionary, guessing, study preferences, memory, autonomy, note-taking, selective attention, and social strategies. In the same vein, Manuel [14] and Aravind & Rajasekaran [15] investigate the same strategies: determination, memory, cognitive, metacognitive, and social strategies.…”
Section: B Classifications Of Vocabulary Learning Strategiesmentioning
confidence: 99%